Plyometrics: Meningkatkan Power Otot Tungkai dan Under Shoot Atlet Bola Basket - Rachlai Eko Arisetiawan; Andi Fepriyanto; Nugroho Agung Supriyanto (Journal Sport Area, 2020)
The aim of this study was to determine the effect of plyometric exercises in single leg jump and depth on explosive power and under shoot. This study used 18 basketball players. The results showed a significant influence between before and after training in group I plyometric single leg jump to increase power and under shoot results, in group II depth jump was a significant effect between before and after training on increasing power and under shoot, whereas in group III the control had no significant effect on increasing power and under shooting. It can be concluded that the group I plyometric single leg jump and group II depth jump explosive power and under shoot both have a significant influence on basketball athletes.